(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to develop a comprehensive academic framework for a Master’s Program in Research and Development Management, addressing the existing gap in specialized educational programs and the growing need for research leaders who integrate research, managerial, and innovative competencies. The proposed program seeks to equip graduates with the ability to lead multidisciplinary research teams, design and implement effective development projects, and generate tangible institutional and knowledge-based impact that supports innovation and the transition toward a knowledge economy. The study adopted a descriptive-analytical methodology, drawing on a systematic review of relevant literature, educational models, and institutional practices, as well as an analysis of comparable academic and professional programs in diverse contexts. The Backward Design approach was employed in constructing the program’s courses, starting from identifying the intended learning outcomes, through assessment tools, to the design of content and learning activities. The findings emphasize that successful implementation of the program in higher education institutions requires an enabling institutional environment, sustainable funding mechanisms through partnerships and applied research initiatives, and an administrative structure that fosters innovation and continuous improvement. The study recommends that relevant authorities support this direction by strengthening specialized education and professional training in Research and Development Management, as a core driver of sustainable development and national competitiveness.